Battery lifetime prediction - Toh, Wang Yun. (2012)
In an earlier investigation [3], battery charging strategy under floating-charge had shown to have an effect on the performance and lifetime of lead-acid battery. The present project is aimed to discover and understand the effects of different charging methods on the performance and lifetime of lead-acid battery.